The Last Man - Flynn, Vince; Guidall, George (New York : Audioworks, 2012)
When a CIA black ops master with ties to disreputable figures in Afghanistan goes missing, Mitch Rapp is ordered to track down the missing man at all costs and finds himself enmeshed in a dangerous plot involving the interests of numerous countries.
Unabridged.
Compact discs.
Read by George Guidall.
Keywords: United States -- Central Intelligence Agency -- Fiction -- Officials and employees; Rapp, Mitch (Fictitious character) -- Fiction; Intelligence officers -- Fiction; Missing persons -- Fiction; Afghanistan -- Fiction; Suspense fiction; Adventure fiction; Audiobooks